• anonymous
Find the oblique or (slant asymptote) of y = (5x^3 +6x^2) / (5x^2 + 4x + 5) and express your answer in the form y = mx + b, where m and b are constants
  • Stacey Warren - Expert
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
  • chestercat
I got my questions answered at in under 10 minutes. Go to now for free help!
  • anonymous
I've done oblique asyptotes years ago. Maybe I can help you out, there are several steps that you must take. 1) Check if your function is an oblique asyptote my finding the limi as x --> infinity 2) If you end up with infinity, then youhave an oblique asymptote 3) After that divide your function y/x to find m, since y = mx + b; mx = y, m = y/x. Then simplify your expression. 4) Then after finding y/x, which is the slope, subtract it from the original mx to find b , so b = (y - mx) . Remember mx = the new slope that you have found. 5) finally you have the slope + b, so you can then write the equation of the OA. Those were general steps that can help you solve any problem that has an OA, as for your question: \[y = 5x^3 + 6x^2/ 5x^2 + 4x + 5\] , step number (1) divide it by x and you'll get \[y = (5x^3 + 6x^2)/ x(5x^2 + 4x + 5)\] multiply x using the distributive law and you will have : \[y = 5x^3 + 6x^2 /5x^3 + 4x^2 + 5x\] now find the limit of this as it goes to infinity: m = \[\lim_{x \rightarrow \infty} = 5x^3/5x^3\] = 1 After that we need to find b now, we know that b = y - mx, and we have found m = 1, so m = x. Now subtract y ( the original function) from m ( which is x): \[(5x^3+6x^2 / 5x^2 + 4x+ 5 ) - x\] do the simplification and you'll end up with : \[5x^3+ 6x^2 - 5x^3 - 4x^2- 5x/5x^3 + 4x^2 + 5x\] = \[2x^2-5x/ 5x^2 + 4x + 5\] then find the limit of that as x goes to infinity: \[\lim_{x \rightarrow \infty} 2x^2/5x^2 = 2/5\] Finally write your equation in a more decent form: - m = 1 -b = 2/5 so y = x + 2/5 Done :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.